Women's and men's responses to in-work benefits: The influence of younger children - Daniela Andrén; Thomas Andrén (Örebro University School of Business, 2014)
This study examines how the non-targeted earned income tax credit (EITC) introduced in Sweden in 2007 has affected the labor supply of men and women living together in two-adault households and the extent to which children affect related outcomes. Using a structural discrete labor supply model for two adult households, we estimate the impact of the EITC on both labor supply and disposable income separately for households with and without children. Our results suggest that wage elasticities differ for men and women with or without children, a result that is in line with earlier literature. However, women increased their labor supply bu 0.9 percent regardless of children in the household, whereas men with children increased their labor supply by approximately 0.5 percent and those without children increased their labor supply by 0.7 percent.
Keywords: I30; I38; J18; 330; structural discrete labor supply model; EITC; younger children; two-adult households